Changes and Correlation Between Hormones, Immunoglobulins, and Minerals in Blood Serum and Hair of Tianzhu White Yaks of Different Ages and Gender - Yunqi Deng; Bingang Shi; Youpeng Qi; Zhihao Luo; Changze Cui; Shaopeng Chen; Xuelan Zhou; Zhidong Zhao; Xiaolan Zhang; Jiang Hu (Animals)
(1) Background: Hair growth can function as an indicator of an animal’s health and nutritional status, furnishing a valuable means for early diagnosis and timely modifications to management practices, and is influenced by hormones, the immune system, and the levels of minerals within the animal’s body. (2) Methods: In this study, a total of 81 yaks were selected and divided into three groups according to their ages (1–2 years, 3–4 years, 5–6 years), and the concentrations of melatonin, dihydrotestosterone, IgA, IgG, and IgM in their blood serum and the levels of Ca, Mg, Zn, Fe, and P in both their blood serum and hair were detected. (3) Results: The levels of melatonin and dihydrotestosterone in yaks aged 1–2 years were significantly higher than those of other age groups (p < 0.001). In addition, the concentration of melatonin in male yaks was markedly greater than that in female yaks (p < 0.05). When it came to immunoglobulins, the IgA level in 1–2-year-old yaks was strikingly higher than those in yaks aged 3–4 years and 5–6 years (p < 0.05). In terms of mineral elements, the concentrations of calcium, magnesium, zinc, and iron in the blood serum of 1–2-year-old and 5–6-year-old yaks were significantly elevated compared to those in 3–4-year-old yaks. However, there was no notable difference between the 1–2-year-old and 5–6-year-old groups. The correlation analysis showed that there was a significant correlation between DHT and the levels of melatonin and IgA in yaks. Additionally, a significant correlation was observed between IgA and IgG, as well as between IgA and the levels of Fe, Mg, and Ca. It is likely that they jointly regulate the hair growth and immune processes of yaks. (4) Conclusions: There are positive correlations among melatonin, dihydrotestosterone, and IgA in the blood serum and the content of Fe and Mg in the hair to varying degrees, implying these indicators may jointly regulate yak hair growth and immune status. These research findings provide data support for applied research into evaluating the overall health status of yaks through the growth status of hair or by measuring the mineral content in hair in a non-invasive way.